2015
DOI: 10.2147/ndt.s75717
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTOR: a culprit of Alzheimer’s disease?

Abstract: Alzheimer’s disease (AD) is characterized by cognitive impairment in clinical presentation, and by β-amyloid (Aβ) production and the hyper-phosphorylation of tau in basic research. More highlights demonstrate that the activation of the mammalian target of rapamycin (mTOR) enhances Aβ generation and deposition by modulating amyloid precursor protein (APP) metabolism and upregulating β- and γ-secretases. mTOR, an inhibitor of autophagy, decreases Aβ clearance by scissoring autophagy function. mTOR regulates Aβ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 245 publications
(322 reference statements)
0
104
0
1
Order By: Relevance
“…Consequently, mTOR-signaling inhibition is a novel therapeutic target for AD (Z. Cai et al 2015) (Tramutola, Lanzillotta, and Di Domenico 2017). There is still much work to be done in order to decipher the precise mechanisms of L-norvaline regulation of the AKT-mTOR signaling pathway, which is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, mTOR-signaling inhibition is a novel therapeutic target for AD (Z. Cai et al 2015) (Tramutola, Lanzillotta, and Di Domenico 2017). There is still much work to be done in order to decipher the precise mechanisms of L-norvaline regulation of the AKT-mTOR signaling pathway, which is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role mTOR holds in memory formation and the fine balance that may be necessary for mTOR activity to promote cognitive function, it is not surprising to observe that excessive activation of mTOR also may function as a pathological mechanism for cognitive loss and the progression of AD . Down‐stream components of mTOR that include active p70S6K can co‐localize with hyper‐phosphorylated tau deposition in the brains of patients with AD, indicating that p70S6K may assist with the accumulation of hyper‐phosphorylated tau .…”
Section: Mtor and Neurodegenerative Disordersmentioning
confidence: 99%
“…mTORC1 negatively controls the initiation of autophagy, contributing to the formation of pathological protein aggregates. Previous studies [120,121] showed that mTOR activation could downregulate Aβ clearance by inhibiting autophagy functions with the suppression of several signaling pathways including PI3K/Akt, glycogen synthase kinase 3 (GSK-3), AMP-activated protein kinase (AMPK), and insulin/insulin-like growth factor 1 (IGF-1) [122]. In addition, the activation of mTOR contributes to aberrant hyperphosphorylated tau [123].…”
Section: Role Of Rheb In Neurodegeneration In the Hippocampusmentioning
confidence: 99%